Case report: Ultrasound misdiagnoses atypical parathyroid adenoma as malignant thyroid tumor - Hou, Yilin; Zhao, Lei; Sun, Jiayue; Zhang, Yun-Fei (Frontiers in Oncology, 2024)
Atypical Parathyroid Adenoma (APA) is a type of tumor that lies somewhere between parathyroid adenoma and parathyroid carcinoma.It often affects adults over the age of 60, and the clinical symptoms are consistent with those of hyperparathyroidism. This condition has a low occurrence, and its ultrasonographic signs are strikinly similar to thyroid malignant tumors, making it easily misdiagnosed. As a result, a case of APA ultrasonography misdiagnosis admitted to our hospital was recorded in order to serve as a reference point for APA diagnosis .